A greener and cheaper approach towards synthesis of glycerol carbonate from bio waste glycerol using CaO–TiO2 Nanocatalysts - Pradhan G.; Sharma Y.C. (My University, 2025)
In this work we focused on clean catalytic approach of efficient CaO/TiO2 green nano particles derived from waste chicken eggshells with inorganic support TiO2 for glycerol carbonate synthesis. The designed nano catalysts were characterized using several chemical and spectrochemical techniques like XRD, FE-SEM, TGA-DSC, FT-IR BET-BJH methods. The corelation between the basic strength and catalytic activity of synthesized catalyst was tested by Hammett indicator method and found to be one of the important factors for glycerol carbonate synthesis. Under optimized condition of reaction parameters (Temp- 90 °C, time – 180min, DMC: gly molar ratio 4:1 and catalyst loading 3 wt% of glycerol used in reaction in gram) 3:1 CaO/TiO2 mixed oxide showed an excellent performance of 99.3% glycerol conversion and 93.7% of glycerol carbonate yield. The green metrics like Process mass intensity (PMI), and Environmental factor (E-factor), were well studied and obtained as 1.37 mg and 0.082 respectively for the transesterification process with 100% atom utilization (AU). The designed catalyst possessing ideal green chemistry metrics appreciate the manufacturing process of GLC both in industrial and lab scale. The utilization of waste eggshell not only a cheaper and green catalyst but also reduces the amount of waste and its treatment cost which is economically and ecologically friendly. © 2021